1981
DOI: 10.1902/jop.1981.52.12.723
|View full text |Cite
|
Sign up to set email alerts
|

Kielbone in New Attachment Attempts in Humans

Abstract: The purpose of this investigation was to evaluate, in humans, the use of Kielbone as a substitute for fresh autogenous bone in treating periodontal intrabony defects. A total of 92 intrabony defects were treated with a previously described new attachment procedure utilizing free mucosal grafts to cover the intrabony defects following bone grafting. Kielbone was placed in 46 of these defects, while the remaining 46 defects were treated with autogenous bone grafts. The results were evaluated after 6 months by pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It is well known that the surgical removal of the junctional epithelium, or repeated postoperative epithelial curettage, is inefficient (76)(77)(78). Also, other attempts at surgical manipulation for the purpose of delaying the apical migration of the oral epithelium do not seem to have given clinical success beyond that of conventional flap management (63,(79)(80)(81)(82).…”
Section: Healing Of the Supracrestal Root Surface Woundmentioning
confidence: 99%
“…It is well known that the surgical removal of the junctional epithelium, or repeated postoperative epithelial curettage, is inefficient (76)(77)(78). Also, other attempts at surgical manipulation for the purpose of delaying the apical migration of the oral epithelium do not seem to have given clinical success beyond that of conventional flap management (63,(79)(80)(81)(82).…”
Section: Healing Of the Supracrestal Root Surface Woundmentioning
confidence: 99%
“…Clinical (Scopp et al 1966, Older 1967) and histological (Arrocha et al 1968, Nielsen et al 1980, 1981 studies promoted the use of anorganic bovine bone for grafting in intra-osseous defects. In this context, an anorganic xenograft (Bio-Oss s , Geistlich Pharma AG, Wolhusen, Switzerland) was developed for bone regeneration procedures.…”
mentioning
confidence: 99%
“…In the quest to restore lost attachment, a variety of implant materials have been investigated.12 Numerous studies have shown varying degrees of success through the implantation of different forms of bone.3 8 Furthermore, in a study by Caton et al,14 no new connective tissue attachment was seen microscopically when a variety of implanted materials were placed in periodontal defects in rhesus monkeys. A junctional epithelium was always interposed between the new bone and the root surface.…”
mentioning
confidence: 99%